1994
DOI: 10.1029/94jd00228
|View full text |Cite
|
Sign up to set email alerts
|

Climatology of tropospheric ozone in southern Europe and its relation to potential vorticity

Abstract: A climatology of the vertical ozone distribution in the troposphere is obtained by balloon‐borne Brewer‐Mast sondes at the Observatoire de Haute Provence (OHP), southern France (44°N, 6°E, 700 m above sea level), during the period 1984 to 1990. The tropospheric ozone seasonal variation is characterized by a large maximum in spring and summer. A comparison to other ozone sounding stations gives evidence for a meridional ozone gradient in the middle and upper troposphere in Western Europe, with larger ozone valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
72
0
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(86 citation statements)
references
References 51 publications
13
72
0
1
Order By: Relevance
“…Figure 2 shows that the mixing ratio of O 3 increased from ∼40 ppbv at ground to ∼65 ppbv around 8 km, and then increased rapidly above 8 km with a larger variability near the tropopause. Such a mean O 3 distribution is typical for locations in mid-latitudes (Logan, 1994;Beekmann et al, 1994;Thouret et al, 1998b;Cooper et al, 2005). In the PBL the O 3 concentrations increased sharply below 1 km and then remained fairly constant (∼52 ppbv) between 1 km and 2 km.…”
Section: Pooled Statistical Analysismentioning
confidence: 70%
See 1 more Smart Citation
“…Figure 2 shows that the mixing ratio of O 3 increased from ∼40 ppbv at ground to ∼65 ppbv around 8 km, and then increased rapidly above 8 km with a larger variability near the tropopause. Such a mean O 3 distribution is typical for locations in mid-latitudes (Logan, 1994;Beekmann et al, 1994;Thouret et al, 1998b;Cooper et al, 2005). In the PBL the O 3 concentrations increased sharply below 1 km and then remained fairly constant (∼52 ppbv) between 1 km and 2 km.…”
Section: Pooled Statistical Analysismentioning
confidence: 70%
“…While numerous studies were conducted in Europe, North America, and in Japan (Beekmann et al, 1994;Logan, 1985Logan, , 1994Liu et al, 1987;Oltmans et al, 1998;Monks, 2000;Pochanart et al, 2002), there is limited knowledge of the temporal and spatial distribution of tropospheric O 3 in China where rapid urbanization and industrial developments have been taken place in the latest two decades. Previous studies of emissions have projected sharp increases in the emissions of O 3 precursors in China, especially in the fastest growing coastal regions of eastern China (Akimoto and Narita, 1994;Streets et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The first method is based upon the numerous recent studies that have used O 3 :PV ratios as a tracer for stratospheric air and O 3 (e.g., [18,[43][44][45][46]). To calculate stratospheric O 3 mixing ratios we multiple GEOS-5 potential vorticity unit (PVU, 1 PVU = 10 6 K m 2 kg −1 s −1 ) values by an O 3 :PV ratio of 41 nmol mol −1 /PVU.…”
Section: Model-predicted Sources Of Ozonementioning
confidence: 99%
“…This value was chosen as it was derived from a study using TOLNet observations and model simulations to calculate O 3 :PV ratios associated with stratospheric transport at the location of the UAH TOLNet lidar site [18]. This value falls within the range of O 3 :PV ratios of 30-45 nmol mol −1 /PVU reported for stratospheric O 3 in past studies (e.g., [43][44][45][46]). A second method was applied in order to estimate the amount of O 3 measured by TOLNet which is associated with "pure" stratospheric intrusions based on methods described in [45].…”
Section: Model-predicted Sources Of Ozonementioning
confidence: 99%
“…Each particle carries a certain amount of ozone so that initial ozone concentrations follow the relationship with PV: (Danielsen, 1968;Beekmann et al, 1994). Based on ozonesonde data for the lower stratosphere, Stohl et al (2000) found S = 60 (51) ppb/pvu for the month of June (July).…”
Section: Model Descriptionmentioning
confidence: 99%